The Adjustment of China’s Foreign Investment Policy and Law - Lessons for Vietnam - Ngoc Mai, Le Thi (VNU Journal of Science: Legal Studies; Vol 38 No 1, 2022)
In recent years, China's economy has made impressive leaps. The success of China is based on many factors, of which foreign investment is an important factor. Famous as the world's factory, China is a country with great potential to attract investment. In 2020, China was one of the five largest FDI recipients in the world. With reported inflows reaching an all-time high, China continued to be the second-largest FDI recipient after the United States [1]. FDI growth in China continued in 2020, with an increase of 6% to $149 billion, reflecting the country’s success in containing the pandemic and its rapid GDP recovery. The growth was driven by technology-related industries, e-commerce and research and development [2]. These results are due to the process of adjusting laws to be compatible with each stage of the country's development, which are experiences that Vietnam should learn from. In this article, I will clarify the changes in foreign investment policy and law that China has made over the years and propose lessons learned for Vietnam.